2021
DOI: 10.1093/eurpub/ckab120.111
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, shift work and food consumption: what relationship?

Abstract: Background A significant percentage of the population is working on shift work and according to several studies this type of work schedule has been associated with an increased risk of developing some pathologies, such as obesity, which are one of the biggest mortality causes in the world. To understand if the shift work has a negative influence on the workers' diet and if it affects the Body Mass Index. Methods Observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is important to note that each employee serves as a person within the company and a consumer in the consumer market. Although some studies have found that work status will affect employees' consumption behavior, [21][22][23] no studies have focused on the relationship between employees' WFC and their consumption behavior. Based on previous studies, this research is for the first to link WFC with employees' consumption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that each employee serves as a person within the company and a consumer in the consumer market. Although some studies have found that work status will affect employees' consumption behavior, [21][22][23] no studies have focused on the relationship between employees' WFC and their consumption behavior. Based on previous studies, this research is for the first to link WFC with employees' consumption behavior.…”
Section: Introductionmentioning
confidence: 99%